Efektivitas Model Discovery Learning dan Problem Based Learning dalam Rangka Peningkatan Kemampuan Literasi Numerasi Mapel IPAS Kelas IV SD - Priti Agustin; Adi Winanto (Elementary Teacher Education Program, Majalengka University, 2023)
The background of this research is that there are still many teachers who do not understand well how to prepare learning that can improve and prepare students' numeracy literacy. The research aims to determine the difference in the effectiveness of using the model Dıscovery Learnıng and Problem Based Learning in order to increase the numeracy literacy skills of the IPAS class IV SD subject. This research method is a quasi-experimental design type Nonequivalet Control Group Design with the research subjects of all fourth grade students of SD Negeri Salatiga 03. The results of the study obtained that the test results N-Gain Score showing the average value of numeracy literacy ability of experimental class 1 using the model Dıscovery Learnıng of 57.4663% the category is quite effective and the experimental class 2 uses the model Problem Based Learning with an average of 38.5194% ineffective category. Thus, it is concluded that there are differences in the effectiveness of the model Dıscovery Learnıng with models Problem Based Learning in the framework of improving numeracy literacy in IPAS class 4 SD subjects.